Cabool (1842) d’Alexander Burnes : du récit de voyage au plaidoyer politique ? - Nadine André (Revue LISA)
This article intends to analyse the content of the narrative of the mission to Kabul (1836-1838), which was aimed at a wide readership, and tries to assess its author’s true intentions as the occupation of the Afghan capital dragged on. It deals with the need to make the Indian subcontinent’s north-west frontier area secure, to maintain a delicate balance between the frontier’s neighbouring states, to counter the threat represented by Persia and Russia while at the same time considering these issues within the broader context of British-Russian relations. It also aims at considering to what extent the British officer’s depiction of the countries he visited was consistent with or differed from the British authorities’ political objectives in the late 1830s.